Answer: 4(3-t)(3+t)
Step-by-step explanation:
after you find the GCF you will have 4(9-t) squared. since 9 is square you will after to put the square root of 9 (which is 3) into the equation when you factor it further. therefore giving you 4(3-t)(3+t). if you un- factored your equation you would get 4(81-t) because 9x9 is 81 not 3. hope this helps. just learned this too lol
(2x +3)(2x-3)= 0
x= -3/2 x = 3/2
Answer:
4sqrt(2) cm
Step-by-step explanation:
a^2 + b^2 = c^2
4^2 + 4^2 = c^2
32 = c^2
sqrt(32) = c
c = 4sqrt(2)
Answer:144
Step-by-step explanation:
It would be, -12.33-7.21 = -19.54